2017
DOI: 10.7863/ultra.15.12021
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Sonographically Estimated Fetal Weight Near Delivery in Pregnancies Complicated With Diabetes Mellitus

Abstract: Although DM alters the biometric measurements of the fetus with increasing thoracoabdominal size, there are no clinically significant alterations in the accuracy of sonography for FW prediction when performed near delivery. Sonography is highly specific for birth weight greater than 4000 g, which is helpful for delivery planning and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…We characterized the diagnostic accuracy of US to detect fetal growth disorders, namely SGA and LGA, in a diverse population of women with both gestational and pregestational diabetes. Similar to other studies in older cohorts and in women without diabetes, the PPV of growth US for LGA in this population was low. This study confirms that the primary value of third‐trimester growth US may be to rule out LGA.…”
Section: Discussionsupporting
confidence: 89%
“…We characterized the diagnostic accuracy of US to detect fetal growth disorders, namely SGA and LGA, in a diverse population of women with both gestational and pregestational diabetes. Similar to other studies in older cohorts and in women without diabetes, the PPV of growth US for LGA in this population was low. This study confirms that the primary value of third‐trimester growth US may be to rule out LGA.…”
Section: Discussionsupporting
confidence: 89%
“…Previous work on the accuracy of ultrasound in the diabetic population to detect LGA fetuses has shown high specificity but low positive predictive value. 7,23 In our study population, over half of the women identified as having an LGA fetus ultimately delivered an infant who was not LGA, demonstrating that ultrasound has a poor positive predictive value for fetal overgrowth; providers should keep this inherent inaccuracy in mind when making decisions regarding labor dystocia with regard to the US-EFW. As for all patients, one way to counteract a potentially misleading effect of an US-EFW on the cesarean rate is to adhere to standard definitions of labor dystocia.…”
Section: Discussionmentioning
confidence: 88%
“…Previous work on the accuracy of ultrasound to detect LGA fetuses has shown high specificity but low positive predictive value. 9 23 In our study population, over half of the women identified as having an fetus with an EFW ≥ 90th percentile on ultrasound ultimately delivered an infant that was not LGA, demonstrating that ultrasound has a poor positive predictive value for fetal overgrowth; providers should keep this inherent inaccuracy in mind when making decisions regarding labor dystocia with regard to the US-EFW. As for all patients, one way to counteract a potentially misleading effect of an US-EFW on the cesarean rate is to adhere to standard definitions of labor dystocia.…”
Section: Discussionmentioning
confidence: 91%